2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611075
|View full text |Cite
|
Sign up to set email alerts
|

Differential entropy feature for EEG-based vigilance estimation

Abstract: This paper proposes a novel feature called differential entropy for EEG-based vigilance estimation. By mathematical derivation, we find an interesting relationship between the proposed differential entropy and the existing logarithm energy spectrum. We present a physical interpretation of the logarithm energy spectrum which is widely used in EEG signal analysis. To evaluate the performance of the proposed differential entropy feature for vigilance estimation, we compare it with four existing features on an EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(49 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…The basic principle of entropy analysis is to extract various entropies from different frequency bands of EEG signals, and these entropies are used to construct the features with the highest discrimination between two types of signals. Previous studies have shown that differential entropy is the most widely used feature in EEG emotion classification ( Shi et al, 2013 ). Differential entropy is the entropy of continuous random variables, which is used to characterize the complexity of continuous random variables and can be defined as…”
Section: Methodsmentioning
confidence: 99%
“…The basic principle of entropy analysis is to extract various entropies from different frequency bands of EEG signals, and these entropies are used to construct the features with the highest discrimination between two types of signals. Previous studies have shown that differential entropy is the most widely used feature in EEG emotion classification ( Shi et al, 2013 ). Differential entropy is the entropy of continuous random variables, which is used to characterize the complexity of continuous random variables and can be defined as…”
Section: Methodsmentioning
confidence: 99%
“…The differential entropy characteristic of a certain frequency band is calculated using (1) shown below. Pi can be regarded as an energy spectrum and is equivalent to the value of signal variance multiplying a constant coefficient N ( N is the length of the fixed time window) [37].…”
Section: A Feature Extractionmentioning
confidence: 99%
“…Differential entropy is defined in Eq. 6,where p(x) represents the probability density function of continuous information (Shi et al, 2013).…”
Section: Differential Entropymentioning
confidence: 99%